HARI SABAT DALAM PANDANGAN GEREJA MASEHI ADVENT HARI KE-TUJUH - Mardhiah Abbas; Ismet Sari; Muhammad Arfin Hasibuan (Studia Sosia Religia, 2021)
This study describes the position of the Sabbath as a day of worship according to the Bible. This research is (Library Research) with Historical, Phenomenological, and Theological approacheswhich is also descriptive and qualitative. The results of this study indicate that the Adventist Church is a fractional sect of Protestant Christianity.They have the distinctive features of the Doctrine and they are just trying to go back to the old Christian tradition and do everything in their life according to the Bible only.The Adventist Church emerged in the 19th century, the Adventist Church originated from the Miller Movement with its prominent figure being William Miller.Miller has attracted the sympathy of many Christians through his Theological investigation of the Day of the Second Coming of Jesus which will occur on October 22, 1884, according to his interpretation of Daniel 8:14. Thus Adventists emerged because the meaning of Adventism itself is the second coming of Jesus.The development of the Adventist Church is very rapid and is known as a health promoter, building health homes and schools and having a printing house such as a publishing house.